Malaria in the State of Amazonas: a typical Brazilian tropical disease influenced by waves of economic development - Sampaio, Vanderson Souza (2015)
Fundação de Medicina Tropical Dr. Heitor Vieira Dourado. Manaus, AM, Brasil / Universidade do Estado do Amazonas. Manaus, AM, Brasil / Fundação de Vigilância em Saúde do Amazonas. Manaus, AM, Brasil.